2020
DOI: 10.3390/genes11030295
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Muscle Tissue Development in Beef Cattle

Abstract: In this review, we highlight information on microRNA (miRNA) identification and functional characterization in the beef for muscle and carcass composition traits, with an emphasis on Qinchuan beef cattle, and discuss the current challenges and future directions for the use of miRNA as a biomarker in cattle for breeding programs to improve meat quality and carcass traits. MicroRNAs are endogenous and non-coding RNA that have the function of making post-transcriptional modifications during the process of preadip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…32 The down-regulation of miR-148a-3p diminishes the bovine myoblast proliferation. 33 Therefore, miR-148a-3p in EVs derived from BMSCs improved ONFH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32 The down-regulation of miR-148a-3p diminishes the bovine myoblast proliferation. 33 Therefore, miR-148a-3p in EVs derived from BMSCs improved ONFH.…”
Section: Discussionmentioning
confidence: 97%
“…Overexpressed miR‐148a‐3p target gene, lysine‐specific demethylase 6b, could promote the osteoblast differentiation 32 . The down‐regulation of miR‐148a‐3p diminishes the bovine myoblast proliferation 33 . Therefore, miR‐148a‐3p in EVs derived from BMSCs improved ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA are non-coding RNA with a maturity length of 18–25 nt; they are ubiquitous in the animal kingdom and are produced by RNA polymerase II transcription. MicroRNA are involved in many different physiological processes in animals (Raza et al, 2020 ), including inhibition of the translation of target genes, affecting mRNA degradation, and regulating the transcription of target genes (Twayana et al, 2013 ). Differentiation of adipocytes is regulated by many miRNA, which are the focus of the current investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already revealed the regulatory effects of human miRNA, including miR-204 (Zhang Z. et al, 2020 ), miR-27a (Kim et al, 2010 ), miR-210 (Ren et al, 2020 ), miR-24 (Liu et al, 2020 ), miR-378 (Duarte et al, 2020 ), miR-149-5p (Khan et al, 2020 ), miR-143 (Zhang L. et al, 2020 ), and miR-145 (Wang et al, 2020 ), on adipogenesis. These classic mechanisms also occur in the adipose tissue, where they have a large impact on the surrounding tissue (Arcidiacono et al, 2020 ; Raza et al, 2020 ). For example, miR-143 promotes the differentiation of adipocytes by directly acting on its target gene, MAP2K5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is named after the “eight hundred miles of Qinchuan” produced in the Guanzhong region of Shaanxi Province [ 25 ]. Compared with other cattle, it has the advantages of tender meat, rich meat taste, and good marble pattern, but it has a slow growth rate, low meat production, and lack of fat deposition [ 26 ]. This study intended to reduce bovine body fat deposition and increase intramuscular fat deposition through molecular level regulation, which is expected to solve the problems of slow growth, low meat production, and insufficient fat deposition in Qinchuan beef cattle [ 27 ].…”
Section: Discussionmentioning
confidence: 99%